Comorbidity and Treatment in Older Psychiatric In-patients—A Retrospective Study in a Chinese Psychiatric Hospital - Liu, Hongmei; Zhu, Yuncheng; Wu, Xiaohui; He, Kan; Wang, Xiaoxiao; Sun, Ping; Zhao, Jie; Yao, Yamin; Ren, Juanjuan; Mao, Ruizhi; Yang, Tao; Yang, Lu; et al. (Frontiers in Psychiatry, 2021)
Background: Comorbid somatic diseases increase the death risk and affect the condition, treatment, and prognosis of older psychiatric patients. We investigated the comorbidity and drug treatment in older patients with psychosis. Methods: This retrospective study used data from 3115 older psychiatric in-patients hospitalized at the Shanghai Mental Health Center Affiliated to Shanghai Jiaotong University School of Medicine, China discharged from 2005 to 2015. Descriptive analyses of patients’ age, sex, treatment drugs, diagnoses (based on ICD-10), and time trend were performed. Results: Patients’ median age was 56 (range, 50-98) years; 1824 (58.6%) were female. The top five first-level diagnoses were schizophrenia (F20) (n = 1818, 58.3%), depressive episode (F32) (n = 457, 14.6%), bipolar affective disorder (F31) (n = 151, 4.8%), manic episode (F30), (n = 143, 4.6%), and vascular dementia (F01) (n = 136, 4.4%). Mental (99.9%), central nervous system (85.2%), digestive system (83.5%), cardiovascular system (72.5%), and anti-infective (59.6%) drugs had the highest prescription rates. The combined use of antidepressants, anti-anxiety, anti-arrhythmic, hormones and endocrine system drugs were significantly higher in female than in male patients, while mood stabilizers and genitourinary system drugs significantly more frequent in men. With increasing age, the F20-F29 patients decreased, while F00-F09 patients increased, with the corresponding changes to prescription in those patients. In comparison to that in 2005-2010, the combined prescriptions for genitourinary and cardiovascular drugs increased between 2011-2015, and F00-F09 and F40-F48 older patients doubled, accordingly anti-Alzheimer's disease drugs and antidepressants more than doubled. F30-F39 patients increased by 49.1%, and anti-anxiety drugs, mood stabilizers, etc. increased by ≥ 50%; F20-F29 older patients decreased by 26.7%, while antipsychotics only increased by 4.4%. Conclusions: This study found the combined drug treatment of somatic diseases, particularly for central nervous, digestive, cardiovascular, respiratory and genitourinary drugs were extremely common among older psychiatric in-patients in China. With increasing age, the F20-F29 patients decreased, while F00-F09 patients increased; the antipsychotics prescriptions decreased, and almost all comorbidity drugs increased. Compared with that in 2005-2010, the older patients with all diagnosis except F20-F29 increased in 2011 to 2015, and the prescriptions for psychotropic, genitourinary, and cardiovascular drugs increased.